1993
DOI: 10.1111/j.1651-2227.1993.tb12506.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial plasma exchange transfusion on blood flow velocity in large arteries of arm and leg, and in cerebral arteries in polycythaemic newborn infants

Abstract: Continuous wave Doppler velocimetry was performed in brachial, femoral and cerebral arteries in four preterm, four small-for-gestational-age (SGA) and eight appropriate-for-gestational age (AGA) polycythaemic newborns before and at 3 and 24 h after partial plasma exchange transfusion and in 18 matched controls at 3 and 24 h after birth. In peripheral arteries, end-diastolic flow velocity was zero in all eight AGA controls, but only in two of the other infants. Consequently, mean flow velocity and red cell tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Our search identified six studies, including a total of 96 neonates, documenting the relationship between polycythemia and cerebral blood flow or velocity in the neonatal population (Table ). Two studies with 21 neonates specifically examined MCA flow velocity: Weissman et al evaluated five polycythemic neonates of a cohort of 151 and showed a significantly lower MCA‐PSV in the polycythemic group than in controls.…”
Section: Principal Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our search identified six studies, including a total of 96 neonates, documenting the relationship between polycythemia and cerebral blood flow or velocity in the neonatal population (Table ). Two studies with 21 neonates specifically examined MCA flow velocity: Weissman et al evaluated five polycythemic neonates of a cohort of 151 and showed a significantly lower MCA‐PSV in the polycythemic group than in controls.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Two studies with 21 neonates specifically examined MCA flow velocity: Weissman et al evaluated five polycythemic neonates of a cohort of 151 and showed a significantly lower MCA‐PSV in the polycythemic group than in controls. Maertzdorf et al evaluated 16 polycythemic neonates undergoing partial plasma exchange transfusion, and demonstrated a clear increase in MCA‐PSV with hemodilution. Five further studies with 91 neonates examined velocity in the anterior communicating, internal carotid and unspecified cerebral arteries.…”
Section: Principal Findingsmentioning
confidence: 99%
See 3 more Smart Citations